Dynamic Quantized Predictive Control for Systems with Time-Varying Delay and Packet Loss in the Forward Channel. (28th June 2015) - Li, Mu; Dou, Lihua; Sun, Jian; Wang, Di
Abstract : Stability and design of a dynamic quantized predictive control system with time-varying delay and packet loss are studied. For the system with time-varying delay and packet loss in the forward channel, a dynamic quantizer that can minimize the quantized output error is designed and a networked quantized predictive control (NQPC) strategy is proposed to compensate for the delay and packet loss. Stability of the NQPC system is then analyzed and a sufficient stability condition is derived and presented in the form of matrix inequality. Finally, both simulation and experimental results are given to demonstrate the effectiveness of the proposed approach.